THE INFLUENCES OF EDUCATION QUALITY AND BOARDING SCHOOL VALUES TOWARD THE INTENTION OF GRADUATE STUDENT TO PERFORM WORD OF MOUTH (Surveys of Graduates Student Kulliyatul Mu'allimin Al-Islamiyah Darussalam Gontor Ponorogo) - Erfan Ariska Putra; Dhika Amalia Kurniawan (Islamic Business and Management Journal, 2021)
Pondok Modern Darussalam Modern has been developed very rapidly from year to year. One of the factors that influence its development is the intention of graduate students of Kulliyatul Mu'allimin Al-Islamiyah Darussalam Gontor Ponorogo to perform Word of Mouth. It is due to the quality of education and impelemntation of pondok values to his students. The purpose of this study was to examine the effect of variable quality of education and the existence of pondok values on the intentions of graduate students of KMI Gontor to perform word of mouth (WOM). The population in this study was graduate students of KMI Gontor in ponorogo woo pertamed word of mouth. Retrieving data using purposive sampling with a sample of 100 respondents. Data analysis techniques include validity, reliability, classic assumption test and multiple linear regrestudents he results showed that the variable quality of education positively students KMI Gontor intention to perform word of mouth and pondok values variable also lodged a positive influence on students of KMI graduates to do word of mouth. Suggestions that can be submitted in relation to the results of this study were as follows: Pondok Modern Darussalam Modern should always increase the factors that positively affects the interest of graduate students of KMI Gontor to do WOM. The variables and indicators in this study are universal and do not bind so further research is expected to add more variables, in order to get results that are able to develop a model in the study.